Where did the marginal land go?: farmers perspectives on marginal land and its implications for adoption of dedicated energy crops - Helliwell, Richard (Elsevier, 2018)
Dedicated energy crops such as miscanthus and short rotation coppice willow were expected by UK policy and academic modelling to be deployed across large swaths of UK marginal lands in response to farm and market level incentives, delivering on bioenergy policy objectives. Yet, this never materialised. This article examines a previously unanalysed component of this policy failure by comparing and contrasting policy and farmer perspectives on marginal land as a suitable site for energy crops. Drawing on qualitative interviews with 32 livestock, arable and mixed farmers in England this research suggests that the policy framing of energy crops on marginal land to resolve sustainability controversies, was translated by the farming community into ‘energy crops are for marginal land’. This acted as a multifaceted barrier to dedicated energy crops due to complex interactions between farmers’ personal and cultural values, on-farm practices, technologies, regulations and market developments. Farmers, never considered their land marginal enough, consequently this policy framing invoked considerable resistance. This highlights the importance of embedding understandings of farmers’ cultural values, on-farm practices, technological change, and tensions between different bodies of regulation when articulating new policy initiatives and the way in which policy narratives translate into practical settings.